The impact of combined gene mutations in inhA and ahpC genes on high levels of isoniazid resistance amongst katG non-315 in multidrug-resistant tuberculosis isolates from China. Issue 1 (December 2018) - Liu, Liguo; Jiang, Fengting; Chen, Lihong; Zhao, Bing; Dong, Jie; Sun, Lilian; Zhu, Yafang; Liu, Bo; Zhou, Yang; Yang, Jian; Zhao, Yanlin; Jin, Qi; et al.
Abstract Whole-genome sequencing was used to analyze the profiles of isoniazid (INH) resistance-related mutations among 188 multidrug-resistant strains ofMycobacterium tuberculosis (MDR-TB) and mono-INH-resistant isolates collected in a recent Chinese national survey. Mutations were detected in 18 structural genes and two promoter regions in 96.8% of 188 resistant isolates. There were high mutation frequencies inkatG, theinhA promoter, andahpC-oxyR regulator regions in INH-resistant isolates with frequencies of 86.2%, 19.6%, and 18.6%, respectively. Moreover, a high diversity of mutations was identified as 102 mutants contained various types of single or combined gene mutations in the INH-resistant group of isolates. The cumulative frequencies ofkatG 315 orinhA -P/inhA mutations was 68.1% (128/188) for the INH-resistant isolates. Of these isolates, 46 isolates (24.5% of 188) exhibited a high level of resistance. A high level of resistance was also observed in 21 isolates (11.2% of 188) with singleahpC-oxyR mutations or a combination ofahpC-oxyR andkatG non-315 mutations. The remaining 17 mutations occurred sporadically and emerged in isolates with combinedkatG mutations. Such development of INH resistance is likely due to an accumulation of mutations under the pressure of drug selection. Thus, these findings provided insights on the levels of INH resistance and its correlation with the combinatorial mutation effect resulting from less frequent genes (inhA and/orahpC ). Such knowledge of other genes (apart fromkatG ) in high-level resistance will aid in developing better strategies for the diagnosis and management of TB.